2015
DOI: 10.1021/acs.nanolett.5b00181
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Directional Excitation of Surface Plasmons by a Single-Element Nanoantenna

Abstract: Directional light scattering is important in basic research and real applications. This area has been successfully downscaled to wavelength and subwavelength scales with the development of optical antennas, especially single-element nanoantennas. Here, by adding an auxiliary resonant structure to a single-element plasmonic nanoantenna, we show that the highly efficient lowest-order antenna mode can be effectively transferred into inactive higher-order modes. On the basis of this mode conversion, scattered opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…In the followings, we consider Au films with thickness of h 1  = 250 nm, slits with width of w 1  = 150 nm, and a Gaussian light beam with wavelength λ  = 700 nm, width of w g  = 7  μ m, and | E | =  p in center. We note that SPPs can also be excited at the upper surface of the Au film when the slit is replaced by a groove and impinged by a light from the top2223. But in this scheme, both the incident and reflected light beams exist above the Au film, which may influence the performance of the corresponding plasmonic lens.…”
Section: Resultsmentioning
confidence: 98%
“…In the followings, we consider Au films with thickness of h 1  = 250 nm, slits with width of w 1  = 150 nm, and a Gaussian light beam with wavelength λ  = 700 nm, width of w g  = 7  μ m, and | E | =  p in center. We note that SPPs can also be excited at the upper surface of the Au film when the slit is replaced by a groove and impinged by a light from the top2223. But in this scheme, both the incident and reflected light beams exist above the Au film, which may influence the performance of the corresponding plasmonic lens.…”
Section: Resultsmentioning
confidence: 98%
“…This assumption simplifies the dependence of the geometric diffraction on the dielectric properties of the metal, and the dependence of the bounded SPP mode on the dielectric properties of the metal-dielectric interface. 38 In Eqn 3, λ is the wavelength of the incident light, ε is the dielectric constant, and n 1 and n 2 represent two refractive indexes of the two media on either side of the interface (see Figure 1a). …”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been shown that the Yagi-Uda antenna, which consists of multiple resonant elements with a spacing distance determined by phase matching conditions and suitably tuned resonance frequencies, can provide strong directivity in the optical domain [17][18][19][20]. The high directivity and efficiencies achieved from these earlier studies stimulated the quest for simpler and more compact geometries that can be fabricated more easily such as: single element nanoantennas [21][22][23][24], bimetallic structures [25], and plasmonic dimers [26]. Important insights have also been gained into the physics of directional scattering by nanoantennas and the role played by dipolar and multipolar sources [27][28][29].…”
Section: Introductionmentioning
confidence: 99%